The Effect of Participatory Budgeting, Information Asymmetry, and Organizational Commitment on Budgetary Slack - Rezza Arlinda Sarwendhi (Universitas Hayam Wuruk Perbanas, 2021)
This study aims to analyze budgetary slack at the management level. This budgetary slack is viewed from several independent variables consisting of participatory budgeting, information asymmetry, and organizational commitment by making managers spread across the city of Surabaya as the research samples. Participatory budgeting is budgeting that involves all levels of personnel in preparing the budget. The opportunity for employees to participate in preparing the budget is closely related to the level of budgetary slack. Information asymmetry is the difference in information held between the principal and the agent. Organizational commitment can be interpreted as a situation where the executives stay in an organization where they work and are committed to their work. This study uses a quantitative approach involving multiple linear regression analysis. The results show that participatory budgeting has no effect on budgetary slack, while information asymmetry and organizational commitment have an effect on budgetary slack.